Respuesta :

Answer:

EG = 41

Step-by-step explanation:

the 2 base angles are congruent then the triangle is isosceles with the 2 legs being congruent , that is

7x + 9 = 5x + 23 ( subtract 5x from both sides )

2x + 9 = 23 ( subtract 9 from both sides )

2x = 14 ( divide both sides by 2 )

x = 7

then

EG = 6x - 1 = 6(7) - 1 = 42 - 1 = 41

Answer:

EG = 41

Step-by-step explanation:

As two base angles are equal, this is an isosceles triangle and the sides opposite to the equal angles are equal.

  7x + 9 = 5x + 23

Subtract 9 from both sides

         7x = 5x + 23 - 9

         7x = 5x + 14

Subtract 5x from both sides.

    7x - 5x = 14

           2x = 14

Divide both sides by 2

             x = 14/2

             x = 7

EG = 6x - 1

     = 6*7 - 1

     = 42 - 1

EG = 41